Isoluminant coloured stimuli are undetectable in blindsight even when they move. - Alexander, I; Cowey, A (2013)
Moving stimuli are the most effective of all in eliciting blindsight. The detection of static luminance-matched coloured stimuli is negligible or even impossible in blindsight. However, moving coloured stimuli on an achromatic background have not been tested. We therefore tested two blindsighted hemianopes, one of them highly experienced and the other much less so, to determine whether they could perform what should be one of the simplest of all motion tasks: detecting when an array of coloured stimuli moves. On each trial, they were presented in the hemianopic field with an array of spots, all red or green or blue or achromatic, in a circular window and on a white surround. The spots moved coherently in the first or second of two short intervals. The subject had to indicate the interval in which the motion had occurred. The luminance of the spots was varied across different blocks of trials, but the background luminance remained the same throughout. For each colour, there was a ratio of luminance between the spots and the white surround at which performance was not significantly better than chance, although at other ratios, performance was good to excellent, with the exception of blue spots in one subject. We conclude that detecting global coherent motion in blindsight is impossible when it is based on chromatic contrast alone.